Survei Kondisi Fisik Siswa Ekstrakurikuler Futsal Putra di SMA Negeri Se-Kota Batu - Syafikri, Mohamad Iqbal; Amiq, Fahrial (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The aim of this research was to determine and assess the level of physical condition of male futsal extracurricular students at State High Schools in Batu City. This type of research uses a quantitative descriptive survey design, the variable studied is the level of physical condition. In this study, the sample taken from the entire population who took part in the men's futsal extracurricular at State High Schools in Batu City amounted to 90 students using a total sampling technique. The results of the physical condition of male futsal extracurricular students at SMAN Se-Kota Batu include the "Very Good" category showing a frequency of 7 students with a percentage of 8%, for the "Good" category showing a frequency of 19 students with a percentage of 21%, while the "Fair" category shows the frequency was 32 students with a percentage of 36%, while the "Less" category showed a frequency of 28 students with a percentage of 31%, and the "Very Less" category showed a frequency of 4 students with a percentage of 4%. The results of this research can be concluded that the physical condition of male futsal extracurricular students at Batu City State High Schools is dominant in the "Enough" category. Suggestions from researchers are that the training material be more varied and that students' physical condition should be paid more attention and needs to be improved.